Development of brain metastases in non-small-cell lung cancer: high-risk features - Nolan Winslow; Jacqueline Boyle; William Miller; Yanzhi Wang; Francois Geoffroy; Andrew J Tsung (CNS Oncology)
Aim: Brain metastases (BM) are a common site of disease progression and treatment failure in non-small-cell lung cancer (NSCLC) and can be identified in up to 30–50% of patients. Although they are common, there is no standardized screening protocol for development of BM in NSCLC. Multiple clinical variables predict increased BM occurrence, and, when present, should be used to initiate screening MRI.Materials & methods: We performed a single center retrospective review of NSCLC patients, examining BM development and overall survival. Available clinical, radiographic and molecular data were reviewed for association with BM and overall survival. A predictive model for BM development was created for multivariate analysis.Results: Risk factors for new BM development in NSCLC included younger age, larger primary lung tumor, Karnofsky performance score (KPS) <70, pre-existing liver or bone metastases, large cell histology and family history of cancer. Factors associated with decreased OS were larger primary lung tumor, extracranial metastases at time of diagnosis, large cell histology and poorly-differentiated carcinoma histology.Conclusion: There are multiple high risk features for developing BM in NSCLC. Each of these factors should routinely be investigated, and presence should prompt brain MRI to allow earlier diagnosis and treatment of BM.